Cross‐generational trans fat intake modifies BDNF mRNA in the hippocampus: Impact on memory loss in a mania animal model. Issue 5 (27th November 2014) - Trevizol, Fabíola; Dias, Verônica T.; Roversi, Katiane; Barcelos, Raquel C.S.; Kuhn, Fábio T.; Roversi, Karine; Pase, Camila S.; Golombieski, Ronaldo; Veit, Juliana C.; Piccolo, Jaqueline; Emanuelli, Tatiana; Rocha, João B.T.; et al.
ABSTRACT Recently, we have described the influence of dietary fatty acids (FA) on mania‐like behavior of first generation animals. Here, two sequential generations of female rats were supplemented with soybean oil (SO, rich in n‐6 FA, control group), fish oil (FO, rich in n‐3 FA) and hydrogenated vegetable fat (HVF, rich in trans FA) from pregnancy and during lactation. In adulthood, half of each group was exposed to an amphetamine (AMPH)‐induced mania animal model for behavioral, biochemical and molecular assessments. FO supplementation was associated with lower reactive species (RS) generation and protein carbonyl (PC) levels and increased dopamine transporter (DAT) levels, while HVF increased RS and PC levels, thus decreasing catalase (CAT) activity and DAT levels in hippocampus after AMPH treatment. AMPH impaired short‐ (1 h) and long‐ (24 h) term memory in the HVF group. AMPH exposure was able to reduce hippocampal BDNF‐ mRNA expression, which was increased in FO. While HVF was related to higher trans FA (TFA) incorporation in hippocampus, FO was associated with increased percentage of n‐3 polyunsaturated FA (PUFA) together with lower n‐6/n‐3 PUFA ratio. Interestingly, our data showed a positive correlation between brain‐derived neurotrophic factor (BDNF) mRNA and short‐ and long‐term memory (r2 = 0.53; P = 0.000/r2 = 0.32; P = 0.011, respectively), as well as a negative correlation between PC and DAT levels (r2 = 0.23; P = 0.015). Our findings confirm that provision of n‐3 or TFA during development over two generations is able to change the neuronal membrane lipid composition, protecting or impairing the hippocampus, respectively, thus affecting neurothrophic factor expression such as BDNF mRNA. In this context, chronic consumption of trans fats over two generations can facilitate the development of mania‐like behavior, so leading to memory impairment and emotionality, which are related to neuropsychiatric conditions. © 2014 Wiley Periodicals, Inc.